The Fabrication and Characterization of a Nickel Nanoparticle Modified Boron Doped Diamond Electrode for Electrocatalysis of Primary Alcohol Oxidation - Stradiotto, Nelson Ramos [UNESP]; Toghill, Kathryn E.; Xiao, Lei; Moshar, Amir; Compton, Richard G. (Wiley-v C H Verlag Gmbh, 2009)
We report the fabrication of a Ni nanoparticle modified BDD electrode and its application in the electrocatalysis of primary alcohol electrooxidation. Modification was achieved via electrodeposition from Ni(NO3)(2) dissolved in sodium acetate solution (pH 5). Characterization of the Ni-modified BDD (Ni-BDD) was performed using ex situ atomic force microscopy (AFM) and high resolution scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDX). Large nanoparticles of nickel were observed on the BDD surface ranging 5 to 690 nm in height and 0.18 mu m(-3) in volume, and an average number density of ca. 13 x 10(6) nanoparticles cm(-2) was determined. The large range of sizes suggests progressive rather than instantaneous nucleation and growth. Electrocatalysis of ethanol and glycerol, was conducted in an alkaline medium using an unmodified BDD, Ni-BDD and a bulk Ni macro electrode. The Ni-BDD electrode gave the better electrocatalytic performance, with glycerol showing the greatest sensitivity. Linear calibration plots were obtained for the ethanol and glycerol additions over concentration ranges of 2.8-28.0 mM and 23-230 mu M respectively. This gave an ethanol limit of detection of 1.7 mM and sensitivity of 0.31 mA/M, and the glycerol a limit of detection of 10.3 mu.M with a sensitivity of 35 mA/M.
Keywords: Nickel nanoparticles; Boron doped diamond; Electrocatalysis; Alcohol oxidation; Fuel cells; Nanoparticles; Alcohols